EVALUTION THE EFFECT OF HEMAZOLE PESTICIDE ON THE VITALITY, GROWTH AND TISSUE CHANGES OF EARTHWORMS - A. K. Aljbouri; S. M. Mahmood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted to show the effect of Hemazole fungicide on the growth and vitality of earthworms when treated with different concentrations of the pesticide (1000,200,40) mg.kgˉ¹ and for periods of (7,14,21,and28) days, a clear decrease was observed in the growth rate of worms treated with the pesticide with the increase in the time period, and the highest decrease in growth was recorded at the concentration of 40 mg.kgˉ¹ amounted to 83.23% during the third period of rearing (21 days), as for the survival of worms, it was noted that young worms were affected by the three concentrations, and the time period for killing worms 100% was observed after (7, 15 and 21)minutes, respectively, while the time period for the death of adult worms was much higher, reaching (72, 30 and 13) minutes. As for the effect of the pesticide on the thickness of the body wall and the occurrence of tissue abnormalities, it was noted that the thickness of the body wall was significantly affected, especially at the concentration of 40 mg.kgˉ¹, where the lowest thickness was 28,333, 170, 39.67 micrometers compared to the control group, which recorded the thickness of the body wall amounted to 56.667, 532.67, 124 Histological abnormalities were also observed, including necrosis in the epidermal layer, a decrease in the thickness of the longitudinal muscles, and flattening or necrosis in the epithelium of the alimentary canal.